Method for preparing a low processing cost in-situ carbide dispersion strengthened mo-14re alloy

CN122941941APending Publication Date: 2026-10-20SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611147169.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-05-13
Filing Date
2026-07-30
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,由于铼价格高昂,合金组织控制难度较大,目前的关键是如何在低铼含量下达到高铼含量的强塑性协同效果

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to a low-cost, in-situ carbide-dispersion-strengthened Mo-14Re alloy preparation method. High-purity Mo powder, Re powder, Zr powder, and C powder are selected and melted using vacuum arc melting technology, followed by casting to obtain an in-situ carbide-dispersion-strengthened molybdenum-based alloy. The mass percentages of each element in the raw materials of this alloy are: 14%≤Re≤14.09%, 0.40%≤Zr≤0.81%, 0.050%≤C≤0.109%, with the balance being the Mo matrix and unavoidable impurities. This invention, while ensuring good mechanical strength of the dispersion-strengthened molybdenum-based alloy, further improves its plasticity and high-temperature thermal stability, making it suitable for use as a structural material in advanced space nuclear reactors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallic materials, specifically relating to in-situ generated carbide dispersion strengthened Mo-14Re alloy and its preparation process. It is an effective process method to improve the strength-elongation ratio and high-temperature thermal stability of molybdenum alloys. Background Technology

[0002] As humanity continues to advance deep space exploration missions, space nuclear reactors, as a revolutionary deep space propulsion technology, have broad application prospects in deep space exploration, orbital satellites, and space surface energy due to their significant advantages such as good environmental adaptability, wide power coverage, and integrated power and energy supply. As the "power core" of a space nuclear energy system, space nuclear reactors will endure extreme conditions such as high temperatures (800-1100 ℃), strong neutron radiation, high-speed liquid coolant scouring, and microgravity during their service life. This places extremely high performance requirements on their structural materials, especially in terms of high-temperature strength, machinability, thermal stability, radiation resistance, and corrosion resistance. Molybdenum alloys, with their outstanding advantages such as high melting point, high thermal conductivity, and resistance to alkali metal corrosion, have become the most promising candidate structural material for space nuclear reactors. However, the intrinsic brittleness caused by the unique electronic configuration of molybdenum alloys leads to poor room-temperature plasticity and insufficient machinability, which greatly limits their engineering applications. The insufficient high-temperature strength and thermal stability of molybdenum alloys severely restrict the reliability of their engineering applications. Furthermore, molybdenum alloys exhibit significant radiation hardening damage under high-dose neutron irradiation, severely hindering the development of space reactors. Therefore, current molybdenum alloys cannot meet the stringent service requirements of space reactors, and there is an urgent need to develop molybdenum alloy materials with comprehensive properties such as high strength and plasticity synergy, high strength and heat resistance, excellent thermal stability, and radiation resistance.

[0003] The introduction of Re (reinforced iron) enables the application of molybdenum alloys in space reactors through the "rhenium effect." Molybdenum-rhenium alloys (Mo-Re) are gradually becoming ideal candidate materials for cladding and core structures in space nuclear reactors due to their excellent high-temperature mechanical properties, radiation resistance, and good compatibility with nuclear fuel. However, intermetallic compounds, specifically the σ and χ phases, tend to precipitate at grain boundaries, resulting in only a slight improvement in the room-temperature plasticity of Mo-Rhenium alloys. Furthermore, the plasticity deteriorates more rapidly with increasing Re content. Low Re content (<15%) weakens the rhenium effect. Among these, Mo-14Re alloys, with their moderate rhenium content, demonstrate outstanding performance in balancing strength, plasticity, and high-temperature resistance, and have received significant attention in several design schemes. However, due to the high price of rhenium and the difficulty in controlling the alloy microstructure, the current key challenge is how to achieve the synergistic effect of high rhenium content with strong plasticity at low rhenium content. Currently, ODS strengthening is the mainstream method, but it still has significant limitations: oxide particles are prone to coarsening at high temperatures, leading to reduced high-temperature strength and thermal stability; moreover, it can cause stress concentration, resulting in decreased plasticity and even cracking; interstitial oxygen segregation at grain boundaries and phase boundaries weakens interfacial bonding strength, leading to embrittlement and affecting processing performance. Therefore, introducing chemically more stable nano-carbide particles as a dispersed reinforcing phase into Mo-14Re alloys is an effective approach. ZrC has advantages such as an extremely high melting point (3540℃), excellent stability, high hardness, and low neutron absorption cross section, and it has the potential to form a semi-coherent interface with the molybdenum matrix, effectively improving phase interfacial bonding and enhancing the alloy's mechanical properties; simultaneously, ZrC can absorb impurity O, reducing the embrittlement effect of O on grain boundaries, improving grain boundary bonding, and enhancing alloy plasticity. Based on this, an innovative design concept of in-situ generation of nano-ZrC dispersion-strengthened molybdenum-rhenium alloy cladding materials is proposed. By generating a diffusely distributed, highly thermally stable, highly hard, and highly melting-point ZrC reinforcing phase in situ within the molybdenum-rhenium solid solution matrix, its strength, plasticity, and high-temperature thermal stability can be significantly improved without substantially increasing its density.

[0004] Therefore, research on the dispersion strengthening mechanism of low-processing-cost Mo-Re alloys, focusing on compositional design, control of the type and distribution of strengthening phases, and optimization of powder metallurgy processes, is an important direction for the development of molybdenum alloy structural materials with independent intellectual property rights and comprehensive properties such as high strength and plasticity synergy, high strength and heat resistance, excellent thermal stability, and radiation resistance. The research results are of great significance for promoting the safe and reliable engineering application of my country's space nuclear energy system and the innovative development of deep space exploration technology. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of existing Mo-Re alloys under high-temperature service conditions. While traditional Mo-14Re alloys possess high melting points and good radiation stability, they are prone to grain coarsening and rapid creep rate increases during long-term service above 1000℃, leading to a decline in mechanical properties and insufficient microstructural stability, making them unsuitable for applications in extreme environments such as aerospace engines and space nuclear reactors. To address these issues, this invention proposes a carbide dispersion-strengthened Mo-14Re alloy and its preparation method. By in-situ generating high-density, nanoscale ZrC particles in the Mo-14Re matrix, and combining this with an optimized vacuum arc melting-homogenization-hot rolling process-heat treatment, a synergistic effect of dispersion strengthening and grain refinement is achieved, significantly improving the alloy's high-temperature strength, creep resistance, and long-term microstructural stability.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A dispersion-strengthened molybdenum-based alloy is characterized by the following mass percentages of each alloying element: 14%≤Re≤14.09%, 0.40%≤Zr≤0.81%, 0.050%≤C≤0.109%, with the balance being the matrix and unavoidable impurities. The introduction of Re reduces lattice friction, increases dislocation slip, promotes cross-slip, and coordinates plastic deformation. Furthermore, Re is a key solid solution strengthening element in molybdenum-based alloys, significantly improving room-temperature brittleness, enhancing plastic deformation capacity, improving high-temperature strength and creep resistance, and enhancing compatibility with nuclear fuels and coolants. It is a crucial component for achieving dispersion strengthening. ZrC nanoparticles, with an average particle size of 30–300 nm, are uniformly distributed within the grains and at grain boundaries, forming a high-strength interface structure with the matrix. This effectively pins dislocations, inhibits grain boundary migration, and prevents grain growth. The alloy ultimately achieves a highly dense, fine-grained microstructure with a relative density ≥98%. It mainly includes the following steps: (1) Raw material selection and preparation: Mo powder, Re powder, Zr powder and C powder with a purity of ≥99.9% are selected. During the smelting process, Zr is deoxidized while C fixes oxygen. The oxygen content of the cast alloy is controlled at an extremely low level to avoid oxide inclusions and grain boundary oxygen embrittlement. (2) Vacuum arc melting: The alloy was prepared using vacuum arc melting technology with a current of 5A and a vacuum degree of 7.0×10⁻⁶. -4 The magnetic stirring current is 5A. The purity of each element is at least 99.9%, and the ingot is remelted nine times to ensure the homogeneity of the composition. (3) Homogenization treatment: After uniformly coating the surface of the ingot with a high-temperature protective coating (Mo-47-32 type) and drying it, repeat the process three times and then homogenize it at 1400±10℃ for 4 h to achieve uniform distribution of alloying elements and eliminate harmful phases generated by dendrite segregation and non-equilibrium solidification. (4) Hot rolling process: The homogenized sample is hot rolled in multiple passes at a rolling temperature of 1250℃, with a single pass deformation of about 5% and a total deformation of about 50% to obtain a fine-grained dense structure. Before hot rolling, a high-temperature protective coating (Mo-47-32 type) is uniformly coated on the sample surface and then dried. The process is repeated three times to ensure that the coating is flat, uniform, and dense, so as to achieve the best protective effect.

[0007] (5) Stress-relieving annealing treatment: The hot-rolled sample is annealed at 1300℃ for one hour to eliminate internal stress and improve machinability; Attached Figure Description The present invention will now be further described with reference to the accompanying drawings.

[0008] Figure 1 The mechanical properties of the MoRe-Zr / C alloy in the as-cast state and after special heat treatment as described in this embodiment; Figure 2 This is a comparison of the room temperature compressive properties of the MoRe-Zr / C alloy described in this discovery embodiment with those of pure Mo and MoRe alloys reported in the literature; Figure 3 This is a summary of the comparison of hardness and compressive properties of the MoRe-Zr / C alloy under different thermal aging conditions described in the embodiments of this discovery; Detailed Implementation The terminology used in this invention is for illustrative purposes only and is not intended to limit the invention. The numerical range should be understood to include all possible values ​​between the upper and lower limits of the range. Any specific value, any interval, and its sub-intervals within the range should be considered to fall within the protection scope of this invention. The upper and lower limits of the aforementioned sub-intervals may be included or excluded independently.

[0009] Unless otherwise stated, all technical and scientific terms used in this specification shall have the meanings commonly understood by one of ordinary skill in the art. While only preferred methods and materials are described herein, similar or equivalent technical solutions may be employed during implementation or testing. All references cited in this specification are incorporated herein by reference to disclose and illustrate methods and / or materials related to those references. In the event of any inconsistency between the cited references and this specification, the content of this specification shall prevail.

[0010] Various modifications and variations can be made to the specific embodiments by those skilled in the art without departing from the spirit and scope of the invention. These modifications and variations are obvious to those skilled in the art and should be considered to fall within the scope of protection of the invention. Therefore, this specification and embodiments are for illustrative purposes only.

[0011] The terms “include,” “including,” “have,” and “contain” used in this article are all open-ended expressions and should be understood as “including but not limited to.”

[0012] The following is a detailed description of various exemplary embodiments of the present invention: This invention proposes a dispersion-strengthened molybdenum-based alloy and its preparation process. The alloying elements are characterized by the following mass percentages: 14%≤Re≤14.09%, 0.40%≤Zr≤0.81%, 0.050%≤C≤0.109%, with the balance being the molybdenum matrix and unavoidable impurities. Re is a key solid solution strengthening element in molybdenum-based alloys, significantly improving room-temperature brittleness, enhancing plastic deformation capacity, increasing high-temperature strength and creep resistance, and improving compatibility with nuclear fuels and coolants. It is a crucial component for achieving dispersion strengthening. Zr and C combine in situ to form nano-sized ZrC carbide particles in the alloy, which are uniformly dispersed in the alloy matrix, effectively achieving carbide pinning strengthening.

[0013] For this dispersion-strengthened molybdenum-based alloy, the present invention proposes a novel preparation process, which is described in the following specific embodiments.

[0014] Example (1) The high-purity element powder of the present invention is prepared by vacuum arc melting.

[0015] (2) Raw material selection and preparation: Mo powder, Re powder, Zr powder and C powder with a purity of ≥99.9% are selected, and the oxygen content of the raw materials is controlled at ≤0.06% to avoid oxide inclusions; (3) Vacuum arc melting: The alloy was prepared using vacuum arc melting technology with a current of 5A and a vacuum degree of 7.0×10⁻⁶. -4 The magnetic stirring current is 5A. The purity of each element is at least 99.9%, and the ingot is remelted nine times to ensure the homogeneity of the composition. (4) Homogenization treatment: After coating the surface of the ingot with three layers of high-temperature protective coating (Mo-47-32 type) and drying, it is homogenized and kept at 1400±10℃ for 4 h to achieve uniform distribution of alloying elements and eliminate harmful phases generated by dendrite segregation and non-equilibrium solidification. (5) Hot rolling process: The homogenized sample is hot rolled in multiple passes at a rolling temperature of 1250℃, with a single pass deformation of about 5% and a total deformation of about 50% to obtain a fine-grained dense structure. Before hot rolling, a high-temperature protective coating (Mo-47-32 type) is uniformly coated on the sample surface and then dried. The process is repeated three times to ensure that the coating is flat, uniform, and dense, so as to achieve the best protective effect.

[0016] (6) Stress-relief annealing treatment: The hot-rolled sample was annealed at 1300℃ for one hour to eliminate internal stress and improve machinability; backscattering observation revealed that a large number of nano-sized ZrC particles were uniformly distributed in the interior of the Mo matrix grains and near the grain boundaries. EDS and selected area electron diffraction (SAED) analysis confirmed that it was a ZrC phase, with no other large-particle oxides precipitated.

[0017] The room temperature compressive properties test results of the alloy of this invention show that the compressive yield strength reaches 922 MPa, the ultimate compressive strength reaches 1589 MPa, and the total compressibility is 28%, exhibiting a good room temperature strength-plasticity synergy, ensuring good machinability without sacrificing strength. Furthermore, within the service temperature range of space reactors (800℃~1100℃), the compressive yield strength after 500 hours of long-term thermal aging still reaches 592 MPa~841 MPa, with a compressibility of 29.3%~30.9%. This indicates that the alloy can maintain high strength-plasticity synergy within the ultra-high temperature service temperature range of space reactors, possessing excellent high-temperature thermal stability. It also demonstrates that the in-situ generated nano-carbide particles have a significant pinning inhibition effect on grain coarsening at high temperatures.

[0018] In summary, the carbide dispersion-strengthened molybdenum-based alloy prepared by the process described in this invention possesses excellent synergy between strength and ductility, high-temperature thermal stability, and machinability, making it suitable for cladding and structural materials applications in high-temperature and high-irradiation environments such as space nuclear reactors. Evaluation indicators: The mechanical properties of the as-cast and specially heat-treated MoRe-Zr / C alloys prepared by the methods described in the examples are as follows: Figure 1 As shown in the figure, its room temperature yield strength significantly increased from ~477MPa / ~536MPa / 579MPa in the as-cast state to ~1028MPa / ~1017MPa / ~923MPa, while the total compressibility reached 25.7% / 21.4% / 27.7%, all exhibiting excellent strength-ductility synergy. The Mo-14Re-0.8Zr-0.1C alloy, with the best strength-ductility match, was annealed at 1200℃ to 1600℃ for one hour, and its microhardness change and room temperature compressive stress-strain curves are shown in the figure. The alloy began to recrystallize at 1300℃ and completely recrystallized at 1500℃. Its recrystallization temperature is significantly higher than that of pure molybdenum (1000℃) and traditional molybdenum alloys (1200℃). The higher complete recrystallization temperature indicates that the alloy has the potential to maintain high strength at higher service temperatures.

[0019] The room temperature compressive properties of the MoRe-Zr / C alloy described in this embodiment are compared with those of pure Mo and Mo alloys reported in the literature, for example... Figure 2As shown. Compared with pure molybdenum and molybdenum alloys in the literature, the alloy prepared by this study with low Re content and low processing cost exhibits higher levels of strength and plasticity.

[0020] The comparison of hardness and compressive properties of the MoRe-Zr / C alloy under different heat aging conditions described in this embodiment is summarized as follows: Figure 3 As shown in the figure, the study found that the MoRe-Zr / C alloy exhibits very high thermal stability. This excellent thermal stability is mainly attributed to the high thermal stability of the ZrC nanoprecipitates and their effective pinning effect on grain boundaries. ZrC has a melting point as high as approximately 3540℃ and hardly undergoes coarsening or dissolution in the temperature range of 800-1200℃. ZrC particles distributed at grain boundaries and within grains effectively inhibit grain boundary migration and grain growth through the Zener pinning effect. In addition, the semi-coherent interface formed by ZrC and the Mo matrix has extremely low interfacial energy, further enhancing the interfacial thermal stability and effectively preventing Ostwald ripening of the particles. At the same time, the purification effect of ZrC eliminates the risk of oxygen embrittlement at grain boundaries, allowing the grain boundaries to maintain high bonding strength even after long-term high-temperature thermal exposure. The synergistic effect of grain boundary purification and ZrC particle pinning is the core mechanism by which the MoRe-Zr / C alloy exhibits excellent thermal stability.

[0021] Mechanical property testing: The mechanical properties at room temperature and high temperature were determined according to GB / T7314-2017 "Metallic materials - Compression test at room temperature" and GB / T 44030-2024 "Metallic materials - Compression test at high temperature".

[0022] Measurement results: At room temperature, the compressive yield strength reaches 922 MPa, the ultimate compressive strength reaches 1589 MPa, and the total compression ratio is 28%. The alloy maintains a compressive yield strength of 592 MPa to 841 MPa and a compressibility of 29.3% to 30.9% even after 500 hours of long-term thermal aging within the space reactor service temperature range (800℃ to 1100℃). This indicates that the alloy retains high strength and ductility synergistically within this ultra-high temperature service range of space reactors, demonstrating excellent high-temperature thermal stability. It also suggests that the in-situ generated nano-carbide particles significantly inhibit grain coarsening at high temperatures. Furthermore, the semi-coherent interface formed between ZrC and the Mo matrix possesses extremely low interfacial energy, further enhancing interfacial thermal stability and effectively preventing Ostwald ripening of the particles. Simultaneously, the purification effect of ZrC eliminates the risk of oxygen embrittlement at grain boundaries, allowing the grain boundaries to maintain high bonding strength even after long-term high-temperature thermal exposure. The synergistic effect of grain boundary purification and ZrC particle pinning is the core mechanism underlying the excellent thermal stability of the MoRe-Zr / C alloy.

[0023] It should be noted that, according to the above embodiments of the present invention, those skilled in the art can fully implement the entire scope of claim 1 and the dependent claims of the present invention, and the implementation process and method are the same as those in the above embodiments. Furthermore, the parts of the present invention not described in detail belong to known technologies in the art. The above description is merely a part of specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. An in-situ carbide dispersion-strengthened Mo-14Re alloy, characterized in that, The alloy comprises, by mass percentage: Re: 14%–14.09%, Zr: 0.40%–0.81%, C: 0.050%–0.109%, with the balance being Mo and unavoidable impurities. The in-situ generated, dispersed ZrC nanoparticles have an average particle size of 30–300 nm and are uniformly distributed within the grains and at grain boundaries. The ZrC particles exhibit a high-strength interfacial structure with the matrix, effectively pinning dislocations and grain boundary migration, thereby inhibiting grain growth. The alloy has a relative density ≥99.3%. The synergistic effect of solid solution strengthening provided by Re dissolving into the Mo matrix and dispersion strengthening by in-situ generated ZrC particles results in excellent compressive properties and long-term structural stability at 800–1100℃.

2. The method for preparing the carbide dispersion-strengthened molybdenum-based alloy according to claim 1, wherein the alloy preparation process includes the following steps: (1) Raw material selection and preparation: Select Mo powder, Re powder, Zr powder and C powder with a purity of ≥99.9% and mix them in proportion; (2) Vacuum arc melting: The alloy was prepared using vacuum arc melting technology with a current of 5A and a vacuum degree of 7.0×10⁻⁶. -4 The magnetic stirring current is 5A. The purity of each element is at least 99.9%, and the ingot is remelted nine times to ensure the homogeneity of the composition. (3) Homogenization treatment: After coating the surface of the ingot with three layers of high-temperature protective coating (Mo-47-32 type) and drying, it is homogenized and kept at 1400±10℃ for 4 h to achieve uniform distribution of alloying elements and eliminate harmful phases generated by dendrite segregation and non-equilibrium solidification. (4) Hot rolling process: The homogenized sample is hot rolled in multiple passes at a rolling temperature of 1250℃, with a single pass deformation of about 10% and a total deformation of about 50%. During the rolling process, a high-temperature protective coating (Mo-47-32 type) is used to protect against oxidation. (5) Stress-relief annealing: Hold at 1300±10℃ for 60 min and cool rapidly to eliminate residual stress, restore plasticity, and further stabilize the microstructure.